Bodies in Agony: Classical Sculpture and Violence in Herman Melville's works - Ronan Ludot-Vlasak (Sillages Critiques)
Instead of pointing to an ideal of harmony and perpetuating a long-lasting tradition initiated by Johann Joachim Winckelmann, allusions to Greco-Roman sculpture in Melville’s works are intertwined with destructive forms of violence. By releasing the darker energies which animate the figure of Apollo – a god “driven by a desire for transgression” in Marcel Détienne’s words – Melville’s writing subverts the immaculate and marmoreal antiquity fantasised by the champions of neoclassicism and opens up an unchartered territory within which agonizing pain and violence might only be glimpsed. Ancient marble works in Typee, Billy Budd or Clarel thus invite us to revisit classical antiquity in the light of its own violence, but they also unveil violence as a spectral force which resists representation and remains – almost – unspeakable.